IMPLEMENTASI PENCATATAN KEUANGAN PADA USAHA KECIL DAN MENENGAH (Studi Kasus pada Telor Asin “ HTM JAYA” di Kabupaten Brebes) - Yusri Anis Faidah; Nurul Mahmuhdah (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
In relation to the government and creditors (banks), the provision of accounting information is also required. The financial recording process is part of the accounting process. If a business wants to last a long time, financial recording or bookkeeping is one element that should not be ignored because business activities of course require financial records / bookkeeping so that every transaction that occurs can be clearly identified. Currently, there are still many small businesses that do not keep financial records in order, so they don't know whether the business they are running is profitable or losing. And if financial records are not carried out properly and correctly it will make the business owner in making any decisions about his business do not have sufficient basis. This research is a descriptive study using qualitative and quantitative approaches to provide an overview. The descriptive research approach in this study is limited to making a description of the phenomena in the field, while the quantitative approach in this study is used to make a description of the implementation of financial recording in accordance with the standards set in salted egg business in Brebes district